Does operating performance really improve following financial institutions merger : a case of Malaysian banks / Wan Mansor Mahmood and Rashidah Mohamad - Mahmood, Wan Mansor; Mohamad, Rashidah (Institute of Research, Development and Commercialization (IRDC), 2007)
This study examines whether the recent bank mergers exercise in Malaysia create synergies reflected in corporate operating performance measures. Four accrual operatingperformance measures are used, i.e. Return on Asset (ROA), Return on Equity (ROE), Profit Margin (PM), and Earning Per Share (EPS). Using a sample of eight anchor banks for a sample period beginning 1997 through 2002, the results show that bank mergers lead to significant post merger improvements, which is consistent with the findings of Neely and Rochester (1987) who also employ accrual performance measures in their study on savings and loan institutions in the us. The findings suggest that even though the mergers are 'forced' in nature, it is able to contribute to the synergistic benefits. The gain in the post-merger operating performance is likely to be due to the provisions for loan loss, which on average is much lower during the post-merger period compared to the pre-merger period. The study also finds that there is an insignificant continuance of pre-merger performance into the post-merger period.